2020
DOI: 10.22271/chemi.2020.v8.i4g.9735
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of temporal variability and trends in seasonal and annual rainfall of Bargarh, Odisha

Abstract: In the recent years the important scientific challenge faced by researchers worldwide is to have a better understanding about climate change at a regional scale. However, for all the regions the changes are unequal and have localized intensity. Therefore it should be quantified at a local scale. Therefore in the current study, an attempt has been made to observe the temporal rainfall variability and trend over a period of 30years (1989-2018) at regional scale for the district Bargarh of Odisha. The detailed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The same was explained by the earlier researchers. Sarkar et al [17] who found that the population of BPH was significantly influenced by the weather parameters in particular, temperature and relative humidity. Chaudhary et al [18] reported the similar results that, temperature was positively correlated with BPH population.…”
Section: Management Of Bph Populationmentioning
confidence: 99%
“…The same was explained by the earlier researchers. Sarkar et al [17] who found that the population of BPH was significantly influenced by the weather parameters in particular, temperature and relative humidity. Chaudhary et al [18] reported the similar results that, temperature was positively correlated with BPH population.…”
Section: Management Of Bph Populationmentioning
confidence: 99%